"Pieśń o Bogu ukrytym" Karola Wojtyły i "Po raz pierwszy modlitwa" Tadeusza Gajcego w świetle Bachelardowskiej poetyki żywiołów (próba interpretacji porównawczej ) = "Song of the Hidden God" by Karol Wojtyla and "First of all prayer" by Tadeusz Gajcy in a light of Bachelard`s poetics of elements (an attempt of co mpara tive interpretation) - Brasse, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
As an altar boy Tadeusz Gajcy served at the morning Mass in the church of St John of God. Karol Wojtyla joined the clandestine seminary at the end of the war. Their work shares metaphysical openness to the experience of faith, devotion to traditional values, as well as ethical maximalism stretched to the point of radicalism.
Keywords: Jan Paweł II, papież (1929-2005); Gajcy, Tadeusz Stefan (1922-1944); John Paul II; poezja polska - 20 w.; polish poetry